2003
DOI: 10.1097/00004691-200304000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Transient Inability to Distinguish Between Faces: Electrophysiologic Studies

Abstract: It is not known with certainty at which level of face processing by the cortex the distinction between a familiar and an unfamiliar face is made. Subdural electrodes were implanted under the fusiform gyrus of the right temporal lobe in a patient who developed an unusual inability to distinguish differences between faces as part of the epileptic aura ("all faces looked the same"). A cortical region located posterior to the epileptic focus was identified that exhibited a maximum evoked response to the presentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
21
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 44 publications
7
21
0
Order By: Relevance
“…In keeping with previous evidence from intracranial recordings (Allison et al, 1994), stimulation studies (Puce et al, 1999;Mundel et al, 2003) and neuropsychological studies (Wada and Yamamoto, 2001), our finding that some regions in the ventral visual pathway are apparently strongly selective for a single class of visual stimuli would seem to argue against the idea that all regions in the ventral visual pathway participate in the representation of each object (Haxby et al, 2001). However, two caveats must be mentioned here.…”
Section: Discussionsupporting
confidence: 83%
“…In keeping with previous evidence from intracranial recordings (Allison et al, 1994), stimulation studies (Puce et al, 1999;Mundel et al, 2003) and neuropsychological studies (Wada and Yamamoto, 2001), our finding that some regions in the ventral visual pathway are apparently strongly selective for a single class of visual stimuli would seem to argue against the idea that all regions in the ventral visual pathway participate in the representation of each object (Haxby et al, 2001). However, two caveats must be mentioned here.…”
Section: Discussionsupporting
confidence: 83%
“…This observation goes beyond our previous report of impairment in recognizing famous faces during a previous implantation in the same region (Jonas et al, 2012) and other electrical stimulation studies reporting impairment in face vs. no face categorization (Chong et al, 2013, see also Afraz et al, 2006 for modulation of face categorization by electrical stimulation of the monkey infero-temporal cortex), impairment in face naming (Allison et al, 1994;Puce et al, 1999) or distortions of the physician's face following electrical stimulation of other faceselective regions (Parvizi et al, 2012;Vignal et al, 2000). More related to our observations, Mundel et al (2003) reported an epileptic patient who stated that "all faces look the same" following electrical brain stimulation of the right fusiform gyrus, suggesting impairment in individual face discrimination. However, the patient reported the same feeling during epileptic seizures, and individual face discrimination was not tested experimentally during electrical stimulation.…”
Section: The Right Ofa Is Critical For Individual Face Discriminationsupporting
confidence: 81%
“…Here, the coordinates of the stimulated region, and most importantly the fMRI and electrophysiological mapping provide decisive evidence that the disrupted functional area is the right OFA. Second, in contrast to subdural grids as used in previous stimulation studies (Allison et al, 1994Puce et al, 1999;Mundel et al, 2003), the Stereo-EEG method (Talairach and Bancaud, 1973) relies on intra-cerebral electrodes which allow us to use low voltage-electrical currents resulting in a very focal effect (e.g., 10 mA in Allison et al (1994) and Puce et al (1999) for 1 to 1.8 mA in the present study). Supporting this claim, high frequency intracerebral stimulation at low voltage is thought to evoke experiential phenomena through the disruption of the neural function near the stimulating electrode (Halgren and Chauvel, 1993).…”
Section: Discussionmentioning
confidence: 99%